Ornithine decarboxylase antizyme 2 (OAZ2) in human colon adenocarcinoma: a potent prognostic factor associated with immunity - Liu, Yiheng; Zhang, Shengjie; Liao, Wenjie; Qian, Jun; Lu, Cuihua; Jin, Li (Scientific reports, 2025)
Despite few studies focusing on the OAZ2 gene in colorectal cancer, its potential role in colon adenocarcinoma (COAD) prognosis and immune modulation remains underexplored. This study examines the expression and mechanistic involvement of OAZ2 in COAD using data from The Cancer Genome Atlas (TCGA) and additional laboratory experiments. We employed uni- and multivariate Cox hazard regression analyses to evaluate its prognostic significance and gene set enrichment analysis (GSEA) to identify related signaling pathways. Our findings demonstrate significantly lower OAZ2 expression in COAD tissues compared to normal counterparts (P < 0.05) and establish its value as an independent prognostic indicator (P < 0.05). Laboratory experiments further revealed that the protein and mRNA levels of OAZ2 are significantly diminished in COAD compared to adjacent normal tissues, while its antagonist AZIN2 shows elevated expression, suggesting a competitive interaction that may regulate tumor behavior. Overexpression of OAZ2 in RKO colorectal cancer cells significantly reduced their proliferation rate and impaired migration, confirming the functional impact of OAZ2 dysregulation in COAD. Gene Set Enrichment Analysis (GSEA) highlighted the involvement of OAZ2 in cardiac muscle contraction and oxidative phosphorylation pathways. Additionally, OAZ2’s association with immune features such as tumor mutational burden (TMB), microsatellite instability (MSI), and immune infiltration underscores its integral role in the tumor microenvironment. These comprehensive findings position OAZ2 as a promising biomarker for COAD prognosis and a potential target for therapeutic intervention, with evidence supporting its regulatory effects on cell dynamics and tumor aggressiveness.